(untitled) (LACCEI, 2024)
This research is aimed at basic education institutions. The purpose of it was to propose an ICT Strategic plan based on Knowledge Management, thus allowing the formation of strategic lines or plans that incorporate teachers in the use of information and communication technologies, and ensure that they themselves are capable of to encourage students to achieve educational objectives. Regarding the methodology used in the research, we worked with a descriptive field study, with a non-experimental design of a quantitative approach, where a sample of 24 teachers was taken. In the same way, various data collection techniques such as interviews and surveys were used, obtaining as a result that the plan demonstrates great effectiveness for effective knowledge management.